Dopamine signaling negatively regulates striatal phosphorylation of Cdk5 at tyrosine 15 in mice - Yamamura, Yukio; Morigaki, Ryoma; Kasahara, Jiro; Yokoyama, Hironori; Tanabe, Akie; Okita, Shinya; Koizumi, Hidetaka; Nagahiro, Shinji; Kaji, Ryuji; Goto, Satoshi (Frontiers in Cellular Neuroscience, 2013)
Striatal functions depend on the activity balance between the dopamine and glutamate neurotransmissions. Glutamate inputs activate cyclin-dependent kinase 5 (Cdk5), which inhibits postsynaptic dopamine signaling by phosphorylating DARPP-32 (dopamine- and cAMP-regulated phosphoprotein, 32 kDa) at Thr75 in the striatum. c-Abelson tyrosine kinase (c-Abl) is known to phosphorylate Cdk5 at Tyr15 (Tyr15-Cdk5) and thereby facilitates the Cdk5 activity. We here report that Cdk5 with Tyr15 phosphorylation (Cdk5-pTyr15) is enriched in the mouse striatum, where dopaminergic stimulation inhibited phosphorylation of Tyr15-Cdk5 by acting through the D2 class dopamine receptors. Moreover, in the 1-methyl-4-phenyl-1,2,4,6-tetrahydropyridine mouse model, dopamine deficiency caused increased phosphorylation of both Tyr15-Cdk5 and Thr75-DARPP-32 in the striatum, which could be attenuated by administration of L-3,4-dihydroxyphenylalanine and imatinib (STI-571), a selective c-Abl inhibitor. Our results suggest a functional link of Cdk5-pTyr15 with postsynaptic dopamine and glutamate signals through the c-Abl kinase activity in the striatum.